The Achievements of Morocco Following the Joint Organization of the 2030 FIFA World Cup with Spain and Portugal - El Kiasse, Rafik (European Journal of Applied Sciences, 2025)
The joint organization of the 2030 FIFA World Cup between Morocco, Spain, and Portugal represents a major opportunity for Morocco’s economic, social, and infrastructural development. This article examines the country's main achievements, particularly in terms of infrastructure investments, tourism development, sports diplomacy, and socio-economic impact. Through an in-depth analysis of available data and case studies, we highlight the direct and indirect benefits of this event for Morocco. Additionally, we use the 2010 FIFA World Cup hosted by South Africa as a case study to predict the impact of the 2030 tournament.